2006
DOI: 10.1007/s10544-006-8305-2
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of interaction between two neutralizing monoclonal antibodies and SARS virus using biosensor based on imaging ellipsometry

Abstract: Two neutralizing human scFv, b1 and h12 were identified initially using ELISA,employing highly purified virus as the coating antigen. The biosensor technique based on imaging ellipsometry was employed directly to detect two neutralizing monoclonal antibodies and serial serum samples from 10 SARS patients and 12 volunteers who had not SARS. Further, the kinetic process of interaction between the antibodies and SARS-CoV was studied using the real-time function of the biosensor. The biosensor is consistent with E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 30 publications
0
35
0
Order By: Relevance
“…Discrete grayscale above the capture antibody control [13] was used as various cut-off level to obtain TP, FN, TN and FP when pathology test was used as reference criterion. The TPF, FPF and Youden's index were then calculated, as shown in Table 3.…”
Section: Preliminary Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Discrete grayscale above the capture antibody control [13] was used as various cut-off level to obtain TP, FN, TN and FP when pathology test was used as reference criterion. The TPF, FPF and Youden's index were then calculated, as shown in Table 3.…”
Section: Preliminary Applicationmentioning
confidence: 99%
“…Compared with above methods, biosensor based on imaging ellipsometry (BIE) [8] has the advantages of labelfree, rapid, and high through-put analysis [9][10][11]. It has many applications especially in biomedical field [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Previous work theoretically and empirically verifies that it can be used in many fields of bioassay including specific combination of antigen-antibody, virus examination, and biomarker measurement. [19][20][21][22]31,38 In this study, a one-step immunoassay for CA19-9 utilizing BIE is demonstrated. The results are also compared with ECLIA by correlation analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Developed in 1995 (Jin et al, 1996(Jin et al, , 1995, the biosensor based on imaging ellipsometry (BIE) employs a protein analysis technique that combined high spatial resolution imaging ellipsometry with multi-protein microarray. BIE has been mainly applied to biomedical fields, such as (1) biomolecule interaction (Qi et al, 2006a;Wang and Jin, 2003b). (2) Hormone detection (Zhao et al, 1998).…”
Section: Introductionmentioning
confidence: 99%